Keberhasilan Usahatani Kopi (Coffea arabica) Melalui Dinamika Kelompok Dan Manajerial Petani - Muhamad Yusuf; Dety Sukmawati; Euis Dasipah (Paspalum: Jurnal Ilmiah Pertanian, 2020)
Coffee was one of the important plantation commodities in the national economy. This can be seen from the role of the coffee plantation sector in providing employment plants, providing the State's foreign exchange through exports. One of the goals of coffee farmers in managing their farming was to make a profit. In achieving this goal, farmers face several obstacles. By joining farmers in a farmer group forum can help explore the potential, solve the farming problems of its members, thus farmer groups have a strategic position in realizing quality farmers. The research was conducted in Sukasari Subdistrict, Sumedang Regency with the unit (subject) of analysis being 70 farmers who cultivated coffee in the harvest season from January to March 2020 Hypothesis testing. path. There was a positive relationship between the dynamics of farmer groups and farmer management. This was evidenced by the correlation value between the dynamics of farmer groups (X1) and managerial farmers (X2) which reached 84.1%. The better the group dynamics, the better the farmer's managerial, which consists of technical skills and business / skills aspects. The dynamics of farmer groups and farmer managerial influences positively on the success of coffee farming. the higher the value of farmer group dynamics (X1) and farmer managerial (X2), the effect on the increase in farming (Y).